Eksperimen recycle limbah kain pre-konsumsi sisa industri sebagai material elemen interior - Djunaidi, Auryn Putri Catherina (Institut Seni Indonesia Yogyakarta, 2024)
In Indonesia, there are several clothing industries that are already engaged in recycling their textile waste. However, it is mostly done by MSMEs. Fabric waste processing generally results in handicraft or art products. Pre-consumer textile waste consists of various types of fabric left over from the cutting or production process of clothing. The huge amount of fabric waste generated by factories can be processed into re-fiber that is soft and lightweight like cotton. This material is easy to mix with other materials to create processed materials for interior products. This research focuses on the potential of processing fabric waste into fibers mixed with other materials into new materials. The method applied in this research is experimentation. The trial gives an idea of the quality and optimization of the application of the material which is expected to be a support for interior products that are ecological, strong, aesthetically valuable and economically valuable. The findings of this research are panel materials that are expected to be used as decorative elements in space, as well as supporting furniture.